The Rise of Private Actors in the Space Sector - Vernile, Alessandra (SpringerBriefs from the European Space Policy Institute,, 2018)
This book provides a broad set of information and data on the rise of private actors in the space sector, organized into different topics covering the various trends that have shaped the space sector during the last decade. The book, written in a descriptive fashion, concludes with recommendations for future analytical research on the topic.